2006
DOI: 10.1158/1078-0432.ccr-05-2253
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Trial of Vaccination of CA9-Derived Peptides for HLA-A24-Positive Patients with Cytokine-Refractory Metastatic Renal Cell Carcinoma

Abstract: Purpose: A phase I peptide vaccination trial was done in patients with progressive cytokinerefractory metastatic renal cell carcinoma (RCC) to assess both the toxicity and capability to induce immune responses of three peptides (CA9p219-227, p288-296, and p323-331) derived from CA9, a tumor-associated antigen ubiquitously expressed in RCC. Experimental Design: Twenty-three patients positive for human leukocyte antigen (HLA)-A24 with histologically confirmed RCC were enrolled. Eligibility included progressive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 27 publications
1
64
0
Order By: Relevance
“…Furthermore, directing the immune response to recently identified tumor-associated antigens such as MUC1 (38), carbonic anhydrase IX-G250MN (CA9) (60) or survivin (61) in RCC cancer patients should also be progressed in order to improve the efficacy of such cell therapy strategies. Our data also prompt to consider re-evaluating the use of IL-2 in gene and cell therapies of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, directing the immune response to recently identified tumor-associated antigens such as MUC1 (38), carbonic anhydrase IX-G250MN (CA9) (60) or survivin (61) in RCC cancer patients should also be progressed in order to improve the efficacy of such cell therapy strategies. Our data also prompt to consider re-evaluating the use of IL-2 in gene and cell therapies of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HLA-A * 0201 restricted T cell epitopes derived from G250/CAIX were identified, eliciting peptide-specific CTLs both in vitro and in vivo (19,48). Clinical phase I/II vaccination trials with G250/CAIX-derived peptides for patients with advanced renal cell carcinoma revealed to be safe and feasible with no gastrointestinal hepatic toxicity observed despite CAIX expression in large bile duct epithelium and gastric mucosal cells (49,50). In the study of Uemura et al, most of the patients developed peptide specific CTLs and/or immunoglobulin G reactive to the peptides and showed clinical responses (49).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, both interferon alpha and IL-2 are toxic, and the large majority of individuals who receive them derive no benefit. Efforts to develop more sophisticated immunotherapy platforms for this disease, including newer cytokine therapy (Alatrash et al, 2004), vaccine therapy (Uemura et al, 2006;Ernstoff et al, 2007), and nonmyeloablative transplantation (Childs et al, 2000;Artz et al, 2004;Rini et al, 2006), have been reported. Although these approaches have demonstrated tantalising indications of efficacy in a small group of individuals, they have not reached the threshold of therapeutic efficacy or safety.…”
mentioning
confidence: 99%